The Effect of Problem Based Learning Assisted by Liveworksheet for Critical Thinking on Senior High School - Mila Rosa Angraini; Chairatul Umamah; S.Ida Kholida (Universitas Nurul Huda, 2026)
This study aims to examine the effect of Problem Based Learning (PBL) assisted by Liveworksheet for critical thinking skills on senior high school. This study employed a quasi-experimental method with a pretest-posttest control group design. The research participants consisted of 36 students in the experimental class and 36 students in control class using purposive sampling technique. The research data were obtained through a critical thinking skills test and a student response questionnaire. The average pretest score of the experimental class was 43.61, which increased to 64.86 for posttest. Meanwhile, the average pretest score for control class was 42.36, which increased to 54.72 for posttest. The results showed a significant difference in critical thinking skills between the experimental class and control class, with a significance value of 0.001 (<0.05). Furthermore, the N-Gain value of 0.3655 fell into the medium category, while the effect size value of 0.83 was classified as high. Student responses to the learning process also showed positive results, with an average percentage of 85%. generally, students who participated in learning using PBL assisted by interactive e-worksheets based on Liveworksheet integrated with PhET simulations achieved higher posttest scores in critical thinking skills compared to students for control class.